EFEK SISA JERAMI DAN TITONIA YANG DIKOMPOSKAN TERHADAP PRODUKSI PADI SAWAH - Gusnidar Gusnidar; Syafrimen Yasin; Mimien Harianti; Tutik Oktaviana (Jurnal Solum, 2018)
The experiment to obtain residue compost of rice straw (S) and tithonia (T) for reduce commercial fertilizers (CF) input and that effect for rice production. This research was arranged in Completely Randomized Block Design (RBD) with three replications of six treatments.  The residue treatments are; A (input Urea 200 kg ha-1 (Ru) + SP-36 100kgha-1 (Rp)+KCl 75 kgha-1 (Rk)), B (Ru+2Rp), C (S  5 tonsha-1+ R), D ( S 5 tonsha-1+Ru+Pstarter (Ps)), E (T, 2,.5 tonsha-1 + J,  2,.5 tonsha-1 + 75%Ru+Ps), F (T, 2,.5 tonsha-1 + J,  2,5tonsha-1 +50%Ru+Ps).   Data of research were statistically analysed.  If the F-calculated was significantly different, they would be further analysed using LSD 0.05. The results showed that residue of T, 2,5 tonha-1 could reduce CF by 50 kg  Ureaha-1 (25% R), 75 kg KCl  ha-1 (100% R) and 90 kg SP-36ha-1 (90% R) with production 6,66 tonsha-1 Husk Rice (HC).  If it is based on farmer tradition, residue of T could reduce CF by 50 kg Ureaha-1 (25% R), and 190 kg SP-36 ha-1 0.95.Key words : compost, residue, rice, straw, tithonia